Human rights in global politics - Dunne, Timothy; Wheeler, Nicholas J. (Cambridge University Press, 1999)
There is a stark contradiction between the theory of universal human rights and the everyday practice of human wrongs. This timely volume investigates whether human rights abuses are a result of the failure of governments to live up to a universal human rights standard, or whether the search for moral universals is a fundamentally flawed enterprise which distracts us from the task of developing rights in the context of particular ethical communities. In the first part of the book chapters by Ken Booth, Jack Donnelly, Chris Brown, Bhikhu Parekh and Mary Midgley explore the philosophical basis of claims to universal human rights. In the second part, Richard Falk, Mary Kaldor, Martin Shaw, Gil Loescher, Georgina Ashworth and Andrew Hurrell reflect on the role of the media, global civil society, states, migration, non-governmental organisations, capitalism, and schools and universities in developing a global human rights culture.